(untitled) (Pursuits: A Journal of English Studies, 2025)
This short research article explores the issues of race and injustices, taking Toni Morrison’s novel Love as a primary data pool. Published in 2003, it shows how Black women are still struggling for survival and identity. These women in the novel are found forging bonds to fight injustices and save dignity. This article, by drawing theoretical insights from various theorists like Andrea O’ Reilly, Joanne McCarthy, Barbara Christian, Elizabeth Abel, and the like, the study sheds light on the techniques or tactics that these black women use to survive, in their search for self-determination, and emancipation. Black women’s identities and their battles in patriarchal societies form the core of this examination. Observing Morrison’s depiction of female characters and her complex depiction of race, gender, and love in American culture, this article explains how Morrison’s work has redefined black women’s experiences and responsibilities.